The Effectiveness of the Socio-Scientific Issues (SSI) Approach on Senior High School Students’ Critical Thinking in Chemistry: A Literature Review - Pratiwi, Ni Kadek Mira; Wijaya, Komang Jnani; Redhana, I Wayan (Hydrogen: Jurnal Kependidikan Kimia, 2026)
21st century learning emphasizes higher-order thinking skills, one of which is critical thinking. However, the 2022 PISA report shows that Indonesian students' achievements in critical thinking and science literacy are still low. One relevant approach to improving students' critical thinking skills is Socio-Scientific Issues (SSI), which is learning based on contextual, complex, controversial, and everyday science issues. Although the Socio-Scientific Issues (SSI) approach has been widely applied in chemistry learning to train higher-order thinking skills, empirical findings are still scattered and have not been systematically synthesized. This study aims to examine the effectiveness of the SSI approach in improving high school students' critical thinking skills through the Systematic Literature Review (SLR) method based on the PRISMA model. A total of 13 empirical articles published between 2016 and 2025 and indexed on Google Scholar, Sinta, and Scopus were analysed. The results of the study show that SSI-based chemistry learning is effective in improving critical thinking skills, particularly in the aspects of argumentation, evidence evaluation, science-based decision making, and problem solving. These findings indicate that the SSI approach has the potential to become the basis for curriculum development and chemistry learning design oriented towards strengthening critical thinking.